Assessment of Babysitters' Awareness of Speech and Language Development: A Pilot Study - Agit Şimşek; Zehra Güneş (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: The aim of this pilot study was to evaluate the awareness levels of in-home babysitters caring for children aged 0–48 months regarding early speech and language development, and to examine the relationship between awareness levels and variables such as educational background and professional caregiving experience. Materials and Methods: This study was designed as a cross-sectional and analytical pilot investigation. A total of 41 in-home babysitters actively providing care for children aged 0–48 months were included. Data were collected using a sociodemographic information form and the Babysitters' Awareness of Speech and Language Development Form, developed by the researchers. The form assessed awareness related to early speech and language developmental milestones, developmental risk indicators, and interactional practices that support language development. Data were analysed using descriptive statistics, group comparisons, and correlation analyses. Results: Overall awareness levels of early speech and language development among participants were found to be in the low-to-moderate range. The mean total awareness score was calculated as 56.1%. Babysitters with higher educational levels demonstrated significantly higher awareness scores compared to those with lower educational attainment (p < 0.05). Although a positive association was observed between professional caregiving experience and awareness levels, this relationship did not reach statistical significance (r = 0.278, p > 0.05). Conclusion: The findings suggest that babysitters may require additional support to accurately recognize developmental milestones and early risk indicators. This pilot study highlights the need to strengthen in-home babysitters' awareness of early speech and language development to support timely identification and appropriate referral processes. The findings provide a scientific basis for the development of structured awareness and educational programs targeting babysitters involved in early childhood care.